Gender differences in the expression of galanin and vasoactive intestinal peptide in oestrogen-induced prolactinomas of Fischer 344 rats - Piroli, Gerardo Gustavo (2004)
We have previously described a sexual dimorphism in oestrogen-induced anterior pituitary tumorigenesis in Fischer 344 rats, with female tumours averaging twice the size of those of males. Neonatal androgenization of female Fischer 344 rats with 100 µg of testosterone propionate reverted that effect, causing a 'male-like' phenotype. The peptides galanin and vasoactive intestinal peptide (VIP) are possible mediators of oestrogen effects on the anterior pituitary, including hyperprolactinemia and lactotroph proliferation. To further extend our previous findings, we investigated the expression of galanin and VIP in the anterior pituitary of control and oestrogenized male, female and neonatally androgenized female Fischer 344 rats. At 3 months of age, rats were deprived of their gonads and divided into control and diethylstilbestrol (DES)-treated groups. In the anterior pituitary of control rats, galanin and VIP immunoreactive cells were absent. However, in DES-treated rats, pituitaries from normal ovariectomized females showed higher number of galanin and VIP positive cells than pituitaries from neonatally androgenized ovariectomized females and gonadectomized males. This pattern correlated with changes in anterior pituitary weight and serum prolactin. Our study suggests that sexual differences in oestrogen-induced pituitary tumorigenesis could be due to the differential expression of galanin and VIP. Furthermore, our data support the fact that neonatal exposure to androgens, as in normal males and androgenized females, may condition the response of the pituitary gland to oestrogens in adult life.